Malnutrition Among Children Under Five Years in Uganda - Mawa, Ratib; Lawoko, Stephen (American Journal of Health Research, 2018)
Malnutrition remains a major cause of morbidity and mortality among children under five years especially in developing countries. The high burden of wasting and stunting among children under five years of age is of great concern to policy makers and public health practitioners in Uganda. Prevention and treatment of malnutrition is a priority in the United Nations 2030 development agenda. This study investigated the risk factors for wasting and stunting among children aged 6-59 months in the general population in Uganda. Secondary data from the 2011 Uganda Demographic and Health Survey was utilised. A sample of 2214 children was studied. Bivariate analysis and multivariate conditional logistic regression was used to determine the association between risk factors and childhood wasting and stunting. 5% and 33.5% of the children were wasted and stunted respectively. Risk factors associated with wasting were lack of maternal education; OR (3.66; 1.22-11.01), maternal underweight -BMI < 18.5 kg/m2; OR (3.39; 1.72 -6.70) and children aged 6-11 months OR (2.20; 1.09 – 4.42). On the other hand, those risk factors associated with stunting included: child`s very small size at birth; OR (2.59; 1.58-4.27), male children; OR (1.5; 1.12 -2.18), children aged 24-35 months (1.17-3.23), maternal height <150cm; OR (7.53; 4.07-13.94) and lack of maternal education; OR (2.47; 1.37-4.44). In conclusion, children’s age and low maternal formal education level predicts wasting. Likewise, children`s male gender, age, size at birth, maternal height and low maternal formal education level also predicts stunting among children under five years of age. This finding suggests that interventions to reduce under-five stunting and wasting in Uganda may benefit from focusing on improvement of maternal nutritional status and formal education.
Keywords: Malnutrition; Wasting; Stunting; Prevalence; Risk Factors; Children Under Five; Uganda